Free-Ridership in Subsidies for Company- and Private Electric Vehicles - Lavan T. Burra; Stephan Sommer; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Consumer subsidies are commonly employed to incentivize the purchase of battery electric vehicles (BEVs), but free-ridership potentially undermines their effectiveness. The present study investigates BEV subsidies in Germany, distinguishing their effect between company- and private cars. Drawing on a panel of high-resolution car registration data, we use the estimates from a Poisson pseudo-maximum likelihood model to predict BEV registrations in the absence of the subsidy. We calculate aggregate free-rider rates of 19% for private cars and 43% for company cars. We further find that the cost of the subsidy per induced BEV among private consumers is exteuro5,400, while it is exteuro7,215 among companies. Overall, the estimates suggest that the subsidy is considerably less cost effective among company cars, which comprise 55% of new BEV sales.
Keywords: H23; L91; Q58; 330; Electric vehicles; consumer subsidy; company cars; free ridership